Misi Kontemporer: Utilitas Teknologi Dalam Misi Kristen Masa Kini - Indarto, Nico Dwiyadi Koes; Nanulaitta, Thomas (Sekolah Tinggi Teologi Sriwijaya, 2024)
This research aims to describe the importance of using or exploiting technology in carrying out the mission of today's church. Contemporary Christian mission cannot be accomplished by itself, even ignoring the importance of technology in it. Based on an investigation using the library research method, this research found that the role of technology in today's Christian Mission is vital and cannot be ignored. However, the use of technology in the context of Christian Missions must also pay attention to Christian ethical principles and consider the consequences of unethical use of technology. With the right strategy and adequate development of technological skills, technology can be an effective tool to assist Christian Missions in sharing the message of God's truth and love.